Long-term results of postoperative and definitive (chemo)radiotherapy in sinonasal carcinoma. Adult Comorbidity Evaluation 27 score as a predictor of survival - Pala, Miloslav; Vrana, Antonin; Novakova, Pavla; Drbohlavova, Tereza; Podlesak, Tomas (Reports of practical oncology and radiotherapy, 2023)
BACKGROUND: The objective was to evaluate the efficacy and toxicity of curative radiotherapy in patients with sinonasal carcinoma and to identify prognostic factors influencing treatment outcomes. MATERIALS AND METHODS: The authors conducted a retrospective study of 61 consecutive patients treated with postoperative or definitive radiotherapy from 2002 to 2018 (median age 59 years, current/former smokers 71%, maxillary sinus 67%, nasal cavity 26%). The majority of patients were diagnosed with locally advanced disease (85% clinical stage ≥ III). Regional cervical metastases were initially diagnosed in 23% of patients. The most common histology was squamous cell carcinoma (61%). Radiation therapy was preceded by radical surgery in 64% of patients. 29 patients received chemotherapy (48%). RESULTS: The median follow-up was 53 months. The median total dose of radiotherapy achieved was 70 Gy. The 5- and 10-year locoregional control, distant control, overall survival, and disease-free survival were 74% and 64%, 90% and 90%, 51% and 35%, and 38% and 25%, respectively. Severe acute toxicity occurred in 36%, severe late toxicity in 23% of patients. Severe unilateral visual impairment occurred in 6 patients, temporal lobe necrosis in 1 patient, and osteoradionecrosis requiring surgery in 2 patients. CONCLUSION: The results of the study demonstrated the high effectiveness of curative treatment in patients with sinonasal carcinoma with long-term locoregional and distant control. The multivariate analysis indicated that N-staging, age, comorbidity score [as assessed by Adult Comorbidity Evaluation 27 (ACE-27)] and initial response to treatment were the strongest prognostic factors.
Keywords: sinonasal carcinoma; prognostic factors; chemoradiotherapy; curative radiotherapy